Transverse vibrations of a clamped rectangular plate or slab with an orthotropic patch - Laura, Patricio Adolfo Antonio (2000)
This study deals with a clamped, rectangular isotropic plate with a centrally located circular and rectangular patch. The optimized Rayleigh-Ritz method is used to determine the fundamental frequency coefficient. An independent solution is derived by means of the finite element technique.